Penguatan Sistem Informasi Pondok Pesantren Nurul Jadid melalui Pendampingan Penggunaan Aplikasi Mahkamah - Nadiyah Nadiyah; Eka Herliana Agustin; Nurul Istiqomah; Rahmawati Rahmawati (GUYUB: Journal of Community Engagement, 2024)
In the face of challenges in processing offense data that still uses manual methods, resulting in inaccuracies and lack of efficiency in information management. To overcome this problem, a Court application system has been developed and implemented which is designed to improve efficiency and accuracy in managing offense data. The service program through intensive mentoring in the use of the Court application with the Participatory Action Research (PAR) method as the implementation approach. Through this method participants are actively involved in the implementation and adaptation process of the system, ensuring that the application is used effectively. Result of this assistance showing participants able to use the Court application  properly and the management of violation data become centralized with the system, optimizing information management at Nurul Jadid Islamic Boarding School. The application will help the court to make decisions because the report feature shows the category of the offense and is complete with the sanctions given to the defendant